2019
DOI: 10.1111/nyas.14168
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on risk factors for esophageal adenocarcinoma: emphasis on Helicobacter pylori infection

Abstract: Gastroesophageal reflux disease (GERD) and the increasing rate of its associated complications, including esophageal adenocarcinoma (EAC), has stimulated a plethora of studies attempting to evaluate provocative and protective factors. Helicobacter pylori (Hp) infection (Hp-I) was initially considered as a beneficial condition in GERD management based on rather limited data. Large-scale regional studies revealed an alternative approach, by suggesting a positive relationship between Hp-I and EAC development. Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…This observational result could include unrecognized confounders, one of which to consider being the overlap between Helicobacter pylori infection (Hp-I) and the conditions treated using a PPI; dyspepsia, peptic ulcer disease and, at least in some populations, gastro-oesophageal reflux disease-Barrett's oesophagusoesophageal cancer sequence are associated with Hp-I and represent the most frequent indications for PPI prescription. 2 Moreover Hp-I is involved in PPI-related disorders discussed by the authors. [1][2][3] The impact of Hp-I with biliary tree diseases has been described.…”
Section: Letter: Helicobacter Pylori In Proton Pump Inhibitor-associamentioning
confidence: 96%
See 2 more Smart Citations
“…This observational result could include unrecognized confounders, one of which to consider being the overlap between Helicobacter pylori infection (Hp-I) and the conditions treated using a PPI; dyspepsia, peptic ulcer disease and, at least in some populations, gastro-oesophageal reflux disease-Barrett's oesophagusoesophageal cancer sequence are associated with Hp-I and represent the most frequent indications for PPI prescription. 2 Moreover Hp-I is involved in PPI-related disorders discussed by the authors. [1][2][3] The impact of Hp-I with biliary tree diseases has been described.…”
Section: Letter: Helicobacter Pylori In Proton Pump Inhibitor-associamentioning
confidence: 96%
“…2 Moreover Hp-I is involved in PPI-related disorders discussed by the authors. [1][2][3] The impact of Hp-I with biliary tree diseases has been described.…”
Section: Letter: Helicobacter Pylori In Proton Pump Inhibitor-associamentioning
confidence: 96%
See 1 more Smart Citation
“…The inconsistencies between H pylori-related oncogenesis data, H pylori status, and progression of the gastro-oesophageal reflux disease (GERD) -Barrett oesophagus (BO) -OAC sequence clearly merits further study. [2][3][4][5][6] The pathogenesis of GERD involves excessive transient lower oesophageal sphincter relaxations (TLOSRs) and imbalance between oesophageal mucosa acidic injury and clearance mechanisms.…”
Section: Letter: Helicobacter Pylori Infection and Its Role In Oesophmentioning
confidence: 99%
“…The recent study also reported an impact of Hp-I related metabolic syndrome on lower gastrointestinal tract oncogenesis 1. There is growing evidence for a potential association between Hp-I and NAFLD and malignancies 2. Hp-I induces overexpression of cyclooxygenase-2 and inflammatory changes in colorectal mucosa leading to cancerogenesis 3.…”
mentioning
confidence: 94%